Home as a Mirror - Wunderle, Jessica (Journal of A Sustainable Global South; Vol 8 No 2 (2024): August 2024, 2024)
Abstract The old traditional architecture of a balinese homes reflect the deeply rooted cultural character of the inhabitants. Balinese homes are often characterised by spiritual beliefs, that reflect Balinese culture and religion. In addition, these traditional homes are often part of communities where a sense of community and togetherness are highly valued.In contrast, people in Europe often plan and build their homes according to personal values and needs. Modern European architecture often emphasises functionality, individuality and aesthetic preferences. The houses are often the result of a personal design decision and reflect the lifestyle of their inhabitants. Attention is often paid to a high degree of individualisation in order to reflect personal expression and philosophy of life.The contrast between traditional Balinese homes and modern European dwellings not only shows different architectural approaches, but also different values and priorities. Whereas in Bali, community and spiritual connectedness take centre stage, people in Europe nowadays value personal freedom, self-development and individuality. These differences in residential architecture illustrate the diversity of human culture and the way in which people design their surroundings to reflect their way of life. At the same time, it also shows that the different living spaces inevitably lead to the development of different characters in the respective inhabitants. Index Terms — changes, personal development, traditions